Rescue of a non-viable accession and RAPD analysis of recovered plants of Arachis retusa - Gagliardi, Rachel Fatima; Pacheco, Georgia Pereira; Oliveira, Carlos Alberto; Caneiro, Leonardo Alves; Valls, José Francisco Montenegro; Vieira, Maria Lucia Caneiro; Mansur, Elisabeth (Pesquisa Agropecuaria Brasileira, 2004)
In vitro regeneration of Arachis retusa was examined for the purpose of germplasm renewal and conservation. Random amplified polymorphic DNA (RAPD) fingerprinting was used to evaluate the genetic stability of plants derived from embryo axes and apical segments. Ten arbitrary decamer primers were screened and five of them were selected. Ninety genomic regions were evaluated, with an average of 18 loci per clone. All amplified segments were monomorphic. The results indicate that recovered plants are genetically stable at the assessed genomic regions and that both regeneration processes are suitable for in vitro germplasm preservation of Arachis species.
Keywords: germplasm conservation; micropropagation; molecular characterization; genetic stability